Horizontal and vertical axis wind turbines on existing jacket platforms: Part 1 – A comparative study. (August 2021) - Mendes, Paulo; Correia, José A.F.O.; Castro, José Miguel; Fantuzzi, Nicholas; Aidibi, Ali; Manuel, Lance
Abstract: The wind resource offshore is often excellent due to a higher average wind speed and lower turbulence intensity. Jacket structures are the most common offshore platforms for extraction of oil and natural gas in relative low water depths. When the offshore resources run out, these structures must be displaced to another area containing underground resources or removed in the case of reaching their design life. Therefore, one possible procedure to reduce the carbon footprint on the planet, allowing society to rely on promising sources of 'clean' energy while salvaging these oil and gas platforms, is to consider the transformation of these oil and gas platforms into offshore wind turbine support structures. The present research focus on the possibility of converting such structures for gas extraction into offshore platforms for wind turbines. In this study, a comparison between the behavior of horizontal and vertical axis wind turbines on the same offshore platform is presented. In this comparison, two different software programs are used: MATLAB and SAP2000. The model proposed is a new simplified tool used to study the structural analysis of the jacket structures, developed and summarized in 10 steps, adopted to evaluate the behavior of the platform with the wind tower configurations.